Corrosion Inhibition of Carbon Steel in 0.5 M H2SO4 by Phtalocyanine Blue. (3rd February 2014) - Valle-Quitana, J. C.; Dominguez-Patiño, G. F.; Gonzalez-Rodriguez, J. G.
Abstract : Phthalocyanine blue dye has been investigated as a carbon steel corrosion inhibitor in 0.5 M sulfuric acid by using polarization curves, electrochemical impedance spectroscopy, and gravimetric tests. Dye concentrations included 0, 100, 200, 400, 600, 800, and 1000 ppm, whereas testing temperatures were 25, 40, and 60°C. Results indicated that phtalocyanine blue is a good corrosion inhibitor with its efficiency increasing with the concentration up to 40°C, but it increases at 60°C. Inhibitor improves the passive film properties and it forms an adherent, compact, protective film, acting, therefore, as an anodic-type inhibitor. At 25 and 40°C the corrosion process was under charge transfer, whereas at 60°C the adsorption/desorption of some species from the metal surface controlled the corrosion process.